IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL TO ENHANCE STUDENTS DEMOCRATIC ATTITUDES: PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN SIKAP DEMOKRATIS SISWA - Zulfa, Lina Nida (LP2M IAI NURUL HAKIM, 2023)
The determination of a learning model that impacts the growth of students' democratic attitudes tends to be overlooked. This results in their low democratic attitudes. This research aims to enhance students' democratic attitudes through the implementation of Problem Based Learning (PBL) as a teaching model. This study is an action research conducted gradually in two cycles. The stages in each cycle include planning, acting, observing, and reflecting. The subjects of this research are fifth-grade students of SDN 7 Cakranegara in the academic year 2022/2023. The research instrument is a valid and reliable questionnaire on democratic attitudes. The results of this research show an improvement in students' democratic attitudes. From the low category of 14 students and the high category of 11 students in the pretest or pre-cycle phase, it increased to 17 students in the high category and 8 students in the very high category in posttest 2 or after the second cycle. Based on the results of the research, it can be concluded that the implementation of Problem Based Learning (PBL) as a teaching model can enhance students' democratic attitudes.